PENGEMBANGAN E-LKPD PROJECT BASED LEARNING BERTEMA 7TH SDGS AFFODABLE AND SUSTAINABLE ENERGY UNTUK SD - Indriyani; Nugraha, Akhmad; Ramadhani Putri, Agnestasia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The global education system faces significant challenges in addressing increasingly complex and dynamic learning needs. Innovations in education, such as developing electronic teaching materials like e-LKPD, are crucial. E-LKPD provides an interactive digital platform that promotes active engagement, collaboration, and problem-solving. This study aims to develop an e-LKPD based on Project-Based Learning (PBL) with the theme of the 7th SDG: Affordable and Sustainable Energy, to enhance students' engagement and understanding of renewable energy. The research employs the Research and Development (R&D) method with the ADDIE development model. During the analysis phase, interviews and document reviews identified needs and challenges in teaching energy at the elementary level. The design phase involved creating the e-LKPD plan, selecting materials, and designing visuals using tools like Canva and Liveworksheets. In the development phase, the e-LKPD was validated by experts in content, media, and pedagogy. Implementation was conducted in two stages with sixth-grade students at SDN Mancogeh. The trial results showed the e-LKPD was highly effective, with suitability ratings of 88.3% in the first trial and 91.56% in the second trial. The final evaluation demonstrated that the e-LKPD significantly supports self-directed and flexible learning, utilizes digital technology for easy access, and fosters 21st-century skills such as critical thinking and collaboration. However, some challenges were noted, including the extended time required for project-based learning, the need for good internet quality, and high production costs. Despite these challenges, the e-LKPD is expected to enhance students' knowledge of renewable energy and contribute to achieving sustainable development goals (SDGs).